Ta có: n2 + 2n + 1 \(⋮\)n + 3
=> n . n + 2n + 1 \(⋮\)n + 3
=> n.(n+3) + 2.(n+3) + 1 - 3n - 6 \(⋮\)n + 3
=> n.(n+1)+2.(n+3) - 5 - 3n \(⋮\)n + 3
=> 5- 3n \(⋮\)n + 3
=> 3n - 5 \(⋮\)n + 3
=> 3.(n+3) - 5 - 9 \(⋮\)n + 3
=> 14 \(⋮\)n + 3
=> n + 3 \(\in\)Ư(14) = { -14;-7;-2;-1;1;2;7;14}
=> n + 3 \(\in\){ -14;-7;-2;-1;1;2;7;14 }
=> n \(\in\){ -17;-10;-5;-4;-2;-1;4;11}
Vậy: n \(\in\){ -17;-10;-5;-4;-2;-1;4;11}
n2+2n+1=(n+3)2-4n-8
vì (n+3)2 chia hết cho n+3=>4n-8 chia hết cho n+3
4n-8=4(n+3)-20
vì 4(n+3) chia hết cho n+3=>20 chia hết cho n+3
=>n+3 thuộc Ư(20)={-20;-10;-5;-4;-2;-1;1;2;4;5;10;20}
=>n thuộc {-23;-13;-8;-7;-5;-4;-2;-1;1;2;7;17}